Is ultrasonographically detected nodule diameter concordant with pathological tumor size?. (June 2017) - Bilginer, Muhammet Cuneyt; Ozdemir, Didem; Baser, Husniye; Dogan, Hayriye Tatli; Yalcin, Abdussamed; Ersoy, Reyhan; Cakir, Bekir
Abstract: Introduction: We aimed to compare preoperative ultrasonographical and postoperative histopathological diameters of differentiated thyroid cancer (DTC) lesions and investigate possible factors that can predict the discordance between two measurements. Methods: Data of patients with histopathologically confirmed DTC were reviewed retrospectively. Nodules evaluated by preoperative US were matched with histopathologically examined nodules. Incidental tumors and nodules that can not be matched in US and histopathology reports were excluded. Preoperative US diameter and postoperative histopathological size were compared and percentage difference between two measurements was calculated for each lesion. Results: There were 607 DTC foci in 562 patients. Mean US diameter was significantly higher than histopathological diameter (21.0 ± 15.6 mm vs 17.3 ± 13.6, p < 0.001). US diameter was higher than tumor size in 444 (73.1%), equal in 15 (2.5%) and lower in 148 (24.4%) nodules. Marginal irregularity was observed in 253 (57%) lesions with US diameter > tumor size and 108 (73%) lesions with US diameter < tumor size (p = 0.010). Rate of nodules with peripheral halo was higher in lesions with US diameter > tumor size (30.6% vs 20.3%, p = 0.015). In nodules with US diameter > tumor size, percentage difference was lower in nodules with microcalcification (p = 0.020) and higher in cytologically benign nodules (p < 0.001). Among nodules with US diameter < tumor size, <1 cm nodules had significantly higher percentage difference compared to 1–1.9, 2–3.9 and ≥ 4 cm nodules (p = 0.005). Conclusion: Ultrasonographically determined diameter is higher than histopathologically determined size in a considerable ratio of DTCs. It might be helpful to consider this discordance while deciding surgical extent in these patients. Highlights: US diameter is higher than histopathological size in 73.1% of thyroid cancers. Difference between US diameter and tumor size is correlated with nodule diameter. Discordance between US and tumor size might be important for surgical extent . Marginal irregularity is related with lower size in US than histopathology. Presence of halo is related with higher size in US than histopathology.